Synthesis of Ibuprofen Monoglyceride in Solventless Medium with Novozym®435: Kinetic Analysis - Marianela Ravelo; Mateusz Wojtusik; Miguel Ladero; Félix García-Ochoa (Catalysts, 2020)
This study investigates the enzymatic esterification of glycerol and ibuprofen in a solventless medium catalyzed by immobilized lipase B from Candida antarctica (Novozym®435). Fixing the concentration of this enzymatic solid preparation at 30 g·L−1, and operating at a constant stirring speed of 720 rpm, the temperature was changed between 50 and 80 °C, while the initial concentration of ibuprofen was studied from 20 to 100 g·L−1. Under these conditions, the resistance of external mass transport can be neglected, as confirmed by the Mears criterion (Me < 0.15). However, the mass transfer limitation inside the pores of the support has been evidenced. The values of the effectiveness factor (η) vary between 0.08 and 0.16 for the particle size range considered according to the Weisz–Prater criteria. Preliminary runs permit us to conclude that the enzyme was deactivated at medium to high temperatures and initial concentration values of ibuprofen. Several phenomenological kinetic models were proposed and fitted to all data available, using physical and statistical criteria to select the most adequate model. The best kinetic model was a reversible sigmoidal model with pseudo-first order with respect to dissolved ibuprofen and order 2 with respect to monoester ibuprofen, assuming the total first-order one-step deactivation of the enzyme, with partial first order for ibuprofen and enzyme activity.